Opening Remarks: Copyrightability in the U.S. Copyright Office - Temple, Karyn A. (The Columbia Journal of Law & the Arts, 2020)
The Copyright Office is really pleased to be cosponsoring this symposium with Columbia Law School on copyrightability. I am especially pleased to be able to do so because copyrightability is something that the Copyright Office knows just a little bit about, having registered and reviewed claims for copyright for nearly 150 years. The Copyright Office analyzes thousands of questions of copyrightability each day. Last year, we examined nearly 650,000 claims to copyright, and by the end of 2019, the Office will have registered more than 38 million claims since 1870. While impressive, these numbers refer only to the number of applications, not to the total universe of works that the Copyright Office has actually reviewed. Indeed, the number of works we have examined over the years soars into the many, many millions. Each time the Copyright Office examines a work, we determine whether it’s copyrightable, of course. These works span the full spectrum of musical works and sound recordings; visual works, including useful articles; and literary works, like books and computer programs. We make more copyrightability decisions than almost anywhere else in the world. For example, in just one week, we make more copyrightability decisions than are received in an entire year by all federal district courts combined.